Experimental investigation of a miniature bladeless turbine - Teo, Chin Guan. (2012)
In this Final Year Project, two miniature Tesla turbines of different sizes were designed and fabricated. One turbine consisted of rotor discs which were 120 mm in diameter, while the other comprised 80 mm diameter discs. Sufficiently strong materials were chosen to suit the purpose of using compressed air as the working fluid. The stator assembly was fabricated using thick acrylic to ensure that failed parts remain contained within the turbine chamber in the event of breakage. The rotor assembly is made up of an aluminium shaft and washers, and steel clamp collars. Standard CDs were used as rotor discs; it had been advised that these CDs would be able to sustain speeds of approximately 20 000 revolutions per minute (rpm). This is in excess of our experimental requirements, where the rpm is not expected to exceed 5000.